1984
DOI: 10.1136/jcp.37.9.1046
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular function and hyperuricaemia in sickle cell disease.

Abstract: SUMMARY Renal insufficiency is common in adults with homozygous sickle cell disease, and the contribution of glomerular failure to the hyperuricaemia which is often a feature of the disease has therefore been investigated. In a study of 64

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Values for creatinine in both Hb AS and Hb SS with out enzyme deficiency were lower than in normal control (p < 0.05). These values are in close agreement with those reported elsewhere [6,13]. However, in Hb AS and Hb SS subjects with G6PD deficiency, the mean levels of creati nine were significantly higher than in subjects without enzyme deficiency (p < 0.05).…”
Section: Hb S S Saudi Subjectssupporting
confidence: 82%
See 1 more Smart Citation
“…Values for creatinine in both Hb AS and Hb SS with out enzyme deficiency were lower than in normal control (p < 0.05). These values are in close agreement with those reported elsewhere [6,13]. However, in Hb AS and Hb SS subjects with G6PD deficiency, the mean levels of creati nine were significantly higher than in subjects without enzyme deficiency (p < 0.05).…”
Section: Hb S S Saudi Subjectssupporting
confidence: 82%
“…Hyperuricemia has been reported to be a common fea ture of homozygous sickle cell disease, occurring in 41% of patients [13][14][15]. This has been attributed to the mark edly increased red cell turnover and decreased renal Values are the mean ± SD.…”
Section: Hb S S Saudi Subjectsmentioning
confidence: 99%
“…Earlier study has shown that an otherwise clinically stable adult SCD patient NS not significant, Y yes, N no, M male, F female, PAH pulmonary arterial hypertension, UA uric acid, PASP pulmonary artery systolic pressure, SS Hemoglobin SS, SC Hemoglobin SC maintains normouricemia by increasing renal UA clearance [16]. Additionally, SCD patients with tubular proteinuria did not have significantly higher UA concentrations than others [17]. Therefore, an elevated UA in SCD patients could point toward its pathophysiological importance.…”
Section: Discussionmentioning
confidence: 90%
“…This finding contrasts with previous studies (Manfredini et al , ; Alsultan et al , ) and could result from the higher level of plasma antioxidant power found in SCA patients, which could have mitigated the AOPP‐specific production pathway in situ (Pialoux et al , ). The greater level of FRAP found in the SCA group compared to healthy subjects may be partly explained by the hyperuricaemia described in SCA patients (Morgan et al , ). Similarly to the FRAP results, and in agreement with the data reported by Manfredini et al () and Rusanova et al (), the activity of the GPX anti‐oxidant enzyme was significantly higher in our SCA patients.…”
Section: Discussionmentioning
confidence: 92%